Basic football strategy an introduction for young players - Dolan, Edward F. 1924-; Lane, John 1932-. (Garden City, N.Y. Doubleday, 1976)
An introduction to both offensive and defensive football strategy as well as the mental and physical preparation necessary to be a successful player.
Keywords: Football -- Juvenile literature; Football